Egg-free low-fat mayonnaise from virgin coconut oil - Mohammed, Nameer Khairullah; Ragavan, Hemala; Ahmad, Nurul Hawa; Meor Hussin, Anis Shobirin (Kemerovo State University, 2022)
Introduction. Mayonnaise is a widely consumed product all over the world. Nowadays, the number of vegetarians, egg allergy cases, and heart diseases are increasing. This makes manufacturers develop alternatives. The research objective was to select the optimal concentration of emulsifiers for egg-free mayonnaise made from virgin coconut oil. Study objects and methods. We produced 20 egg-free mayonnaise samples with different amounts of emulsifiers. We also determined physicochemical properties of the samples, as well as performed proximate and statistical analyses. Results and discussion. The response surface methodology made it possible to define such parameters as viscosity, stability, and firmness as affected by the following concentrations: cashew nut protein isolates - 5-15%, xanthan gum - 0-1%, and modified starch -0-0.5%. The optimal values of emulsifiers were obtained as follows: cashew nut protein isolates - 13 g, xanthan gum - 1.0 g, and modified starch - 0.4 g. The optimized mayonnaise had the following parameters: viscosity - 120.2 mPa.s, stability - 98.7%, and firmness - 25 g. The study revealed no significant differences (P > 0.05) between the actual and predicted data, which confirmed the efficiency of the suggested models. Conclusion. The obtained low-fat egg-free mayonnaise was relatively similar to the traditional commercial products. However, virgin coconut oil should be emulsified with a combination of cashew nut protein isolates, modified starch, and xanthan gum.